Numerical Solutions of Fractional Integral and Fractional Integrodifferential Equations - Gorial, I. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we introduce and discuss an algorithm for the numerical solution of some kinds of fractional integral and fractional integrodifferential equations. The algorithm for the numerical solution of these equations is based on iterative approach. The stability and convergence of the fractional order numerical method are described. Finally, some numerical examples are provided to show that the numerical method for solving the fractional integral and fractional integrodifferential equations is an effective solution method.